Synergy of olive bioactive phytochemicals and probiotic strain in control of Escherichia coli - F. Xavier Malcata (2015)
The increasing market of probiotics from plant matrices justifies the interest on fermented olives not only for their nutritional properties, but also because they contain health-promoting phytochemicals (such as phenolic compounds) that exhibit antibacterial, antiproliferative, anticarcinogenic and anti-inflammatory properties. Additionally, olives have proven a good source and carrier of Lactobacillus strains with probiotic characteristics. However, studies focusing on the combined effect of phenolic compounds with wild probiotic bacteria have not been yet carried out. Hence, the aim of this work was to set up the combination of native olive phenolic compounds, e.g. oleuropein and hydroxytyrosol, on the recommended levels for a daily dose of olives containing probiotic bacteria and their effect on the attachment ability and action against pathogens in situ. Tests on the health benefits of these compounds, viability and adhesion capacity of probiotic bacteria, and consequent biofilm formation, composition and relationship with adhesivity on Caco-2 model were performed. The Caco-2 cell viability results (>140%) show that there is no toxicity effect of both phenolic compounds for the levels considered (0.04 and 0.01%, w/v, for OL and HT, respectively). Conversely, these compounds can inhibit (26-50%) proliferation of human colon adenocarcinoma cells. It became clear that biofilm production on abiotic surfaces is not necessarily associated with adhesivity on biotic surfaces. The strong increase in the adhesion degree of Lactobacillus plantarum 33 after biofilm establishment prompted evaluation of the correlation between biofilm formation and adhesion capacities.